2010
DOI: 10.29333/ejgm/82867
|View full text |Cite
|
Sign up to set email alerts
|

Rifamycin SV Application to Subcutanous Tissue for Prevention of Post-Cesarean Surgical Site Infection

Abstract: Aim

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
0
16
0
1
Order By: Relevance
“…Setting & procedure. The setting where the findings are derived from were mainly public teaching hospitals [41, 52, 57-62, 64, 66] with three based in private hospitals [53][54][55]63]. All the studies were based in single centres.…”
Section: Plos Onementioning
confidence: 99%
“…Setting & procedure. The setting where the findings are derived from were mainly public teaching hospitals [41, 52, 57-62, 64, 66] with three based in private hospitals [53][54][55]63]. All the studies were based in single centres.…”
Section: Plos Onementioning
confidence: 99%
“…[25] The first local application of rifamycin SV, the target agent of this study, was conducted in lung caverns; several subsequent studies have shown its topical use on both animals and wounds that occurred due to human surgery and trauma. [26][27][28][29] In their study, Kaya et al [27] reported that in the tibia defect they created in rats, rifamycin caused significant histological improvement and new bone formation in the group where a bone graft was not used compared to the control group. Iselin et al [28] reported that topical rifamycin is useful for hand injuries, and could control infection and accelerate wound recovery.…”
Section: Discussionmentioning
confidence: 99%
“…In the rifamycin group, the symptoms of infection significantly decreased and the recovery was faster. In a clinical study conducted by Köşüş et al, [29] 1,196 patients who had cesarean incisions were divided into two groups; povidone iodine was applied to patients in the first group preoperatively and postoperatively at the site of incision, while in the second group, the patients were applied rifamycin SV to subcutaneous tissue before closure of skin, in addition to application of povidone iodine. Overall, rifamycin SV applied under the skin decreased infection at the site and the cost of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Rare allergic reactions and a few adverse effects may occur after local application of rifamycin. 14,15 Rifamycins are used for surgical site infection in orthopedic and maxillofacial surgeries and are well tolerated by bone tissue. Previous studies reported rifamycin may positively affect bone tissue, extraction socket healing, and osteomyelitis treatment.…”
mentioning
confidence: 99%